Invasive Disease Caused by Nontypeable Haemophilus influenzae - Jeroen D. Langereis; Marien I. de Jonge (Emerging Infectious Diseases, 2015)
The incidence of severe Haemophilus influenza infections, such as sepsis and meningitis, has declined substantially since the introduction of the H. influenzae serotype b vaccine. However, the H. influenzae type b vaccine fails to protect against nontypeable H. influenzae strains, which have become increasingly frequent causes of invasive disease, especially among children and the elderly. We summarize recent literature supporting the emergence of invasive nontypeable H. influenzae and describe mechanisms that may explain its increasing prevalence over the past 2 decades.